Вербальні та невербальні засоби вираження неправди (на матеріалі сучасної французької мови - Мартинюк, Оксана Миколаївна; Martyniuk, Oksana M. (Національний університет "Острозька академія", 2016)
У статті досліджуються особливості вираження неправди у художньому дискурсі. Проаналізовано основні вербальні та невербальні засоби передачі неправдивої інформації. The article deals with the peculiarities of expression of lie (falsehood) in French discourse. The basic verbal and nonverbal means of transmitting of false information were analsed. The concept of «lie» is a multifaceted phenomenon and is used not onl in science: philosoph, sociolog, pscholog, criminolog, medicine, but also in everda life. False statement is a phenomenon of communication, which is the deliberate distortion of truth, and its goal is to influence the addressee of the message. It was established that the linguistic means of false utterances are expressive vocabular, sntactic compression, repetitions, omission of logicall necessar components, verbosit etc. In some cases, non-verbal means are snonmous to the verbal units and can replace them in the communication process. So, non-verbal means of false statements are pauses, increasing decreasing of the tone, loud and uick, slow and uiet speech, changes of facial expressions, gestures the movement of the bod or its parts. Those signs indicate the emotional distress of the liar. The complex of motives can encourage people to lie. In order to meet the needs, to achieve the goal, the person performs certain actions under external or internal conditions. One of the manifestation of falsehood can be flattering phrases in order to influence the addressee of the message. It was explored that the phenomenon «lie» can be distinguished into active lie (when the person intentionall distorts the truth to tell a lie), passive (when the speaker conceals a false information without telling anthing), and self-deception (when a person who deceives and the recipient of the false message is one person).
Verbal and Non-verbal Means of Expression of Lie (based on Modern French Language)
Keywords: неправда; lie; адресат повідомлення; addressee of the message; вербальні та невербальні засоби комунікації; verbal and non-verbal means of communication